EFEKTIVITAS STRATEGI PEMBELAJARAN DISCOVERY LEARNING DALAM MENINGKATKAN PEMAHAMAN KONSEP SISWA - Farida, Berta Rosalina Silaban; Farida Andriani (STKIP Subang, 2026)
This study aims to examine in depth the effectiveness of the Discovery Learning strategy in improving students' conceptual understanding through a review of various scientific literature. The main problem underlying this research is the tendency of conventional learning patterns to position students as passive recipients of information, resulting in a shallow understanding of basic concepts and easy forgetting. The Discovery Learning strategy is analyzed as a pedagogical solution that provides opportunities for students to be actively involved in organizing, discovering, and constructing their own understanding. The research method used was library research. Data analysis was conducted qualitatively using content analysis and literature synthesis techniques to draw comprehensive conclusions regarding the implementation of this strategy. The results of the literature review indicate that the Discovery Learning strategy is significantly effective in improving students' conceptual understanding compared to traditional learning methods. This effectiveness stems from systematic stages that include stimulation, problem statement, data collection, data processing, verification, and generalization. These findings confirm that students' cognitive engagement in the independent discovery process can improve memory retention and help students connect new concepts to existing knowledge structures. This study concludes that the implementation of Discovery Learning is highly recommended for educators as an effort to create more meaningful and exploratory learning.